Full Spectrum Cannabidiol Oil as a Symptomatic Management Strategy in Geographic Tongue: Case Report with Literature Review - Parise, Guilherme Klein; Silvestre, Ana Caroline; First, Laura Gabriela de Oliveira; Gasparini, Larissa Rodrigues; Schussel, Juliana Lucena (Brazilian Journal of Case Reports, 2026)
To report a case of symptomatic geographic tongue (GT) successfully managed with full-spectrum cannabidiol (CBD) oil, highlighting dose–response dynamics, individualized titration, and clinical outcomes. A 60-year-old female presented with a five-month history of oral burning sympton. Clinical examination revealed multiple atrophic areas with whitish borders on the dorsal tongue. Laboratory investigations were within normal limits except for mildly reduced vitamin D. Prior use of topical corticosteroids provided transient symptom relief. CBD oil (3000 mg/30 mL) was administered sublingually, starting at 5 mg twice daily and titrated weekly according to pain intensity measured by Visual Analog Scale (VAS). The patient experienced significant improvement (VAS reduced from 8 to 2) at 4 drops twice daily. No adverse effects were reported during a three-month follow-up. Although GT generally does not require treatment, symptomatic cases may significantly impact quality of life. The analgesic, anti-inflammatory, and emotion-modulating properties of cannabidiol (CBD) may explain the observed clinical improvement. The non-linear clinical response reinforces the importance of individualized dose titration and careful monitoring. Full-spectrum CBD oil may represent a potential therapeutic approach for patients with persistent GT. Careful titration is essential to optimize outcomes. Further controlled studies are needed to confirm efficacy and establish evidence-based dosing protocols.